Celebrity Endorsement as an Element of Promotion on the Example of Selected Luxury Brands - Pysiewicz, Natalia (Celebrity endorsement jako element promocji na przykładzie wybranych marek luksusowych, 2024)
This work focused on using celebrity endorsement as a promotional strategy in the luxury sector. The goal was to understand the impact of different types of fit between celebrities and brands. Through qualitative case studies and a quantitative experiment, the research showed that image fit had a significant impact on customers’ purchase intention and attitude towards the brand. When the image of a celebrity was in line with the brand identity, it increased authenticity and credibility, which translated into a higher purchase intention and a more positive attitude. Carefully selecting celebrities who match the brand identity is crucial in positively shaping consumer perceptions and behaviours. Celebrity endorsement is proving to be an effective tool for luxury brands to build aspirations and emotional bonds with their target audience.
Pysiewicz, N. (2024). Celebrity Endorsement as an Element of Promotion on the Example of Selected Luxury Brands. W J. Radomska & A. Witek-Crabb (Red.), New Trends in Business Management (s. 91–102). https://doi.org/10.15611/2024.30.7.07
Keywords: celebrity endorsement; fit; image fit; brand attitude; luxury brands; aprobata celebrytów; dopasowanie; dopasowanie wizerunkowe; postawa wobec marki; marki sektora luksusowego